PERAN GURU AKIDAH AKHLAK DALAM MEMBINA AKHLAK SISWA DI MI MA’ARIF - Zhomicx, Omid; Tamami, Rosyid Ridlo (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
Moral development in students is very important to be instilled early, both in the family environment, madrasah and society. Therefore, the role of Akidah Akhlak teachers in fostering the morals of fifth grade students at MI Ma'arif 2 Jatisari is needed. The purpose of the study was to determine the morals of students and to determine the role of Akidah Akhlak teachers in fostering the morals of fifth grade students at MI Ma'arif 2 Jatisari. This research is qualitative research. The research design is descriptive qualitative. Data obtained from observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing. The results showed that: (1) the morals of students in MI Ma'arif 2 Jatisari are quite good, this is evidenced by moral coaching through habituation, namely praying before starting learning, asmaul husna, tahlil, yasin, memorizing short letters, carrying out dhuha and dhuhur prayers in congregation. Not only that, on Islamic holidays, they also organize routine activities in the holy month of Ramadan, namely flash pesantren, payment and distribution of zakat, distribution of takjil and tarawih together. (2) The role of Akidah Akhlak teachers in fostering the morals of fifth grade students at MI Ma'arif 2 Jatisari is good, namely through various roles such as the role of teachers as facilitators, as mentors, as environmental providers, as models, as motivators, and as managers. Keywords: The role of teachers, developing morals, students